Fyn, an important molecule in the brain, is a potential therapeutic target for brain tumours - Xu, Chongxi; Tang, Yi; Lu, Xing; Chen, Ruiqi (Frontiers in Pharmacology, 2024)
Under normal physiological conditions, Fyn, a nonreceptor tyrosine kinase, is involved in signal transduction pathways in the nervous system and in the formation and activation of T lymphocytes. Fyn is a member of the Src family of kinases (SFKs) and plays a role in cell morphogenic transformation, motility, proliferation, and death, which in turn influences the development and progression of various cancer types. SFKs are overexpressed or hyperactive in tumours, and they are engaged in several signalling pathways that lead to tumour development. Inhibition of Fyn can enhance patient outcomes and prolong survival. Thus, Fyn is a desirable therapeutic target in a variety of tumour types. To lay the groundwork for further investigation and targeted therapy in tumours, in this article, we review the most recent findings on the function of Fyn in tumours, with an emphasis on its role in gliomas. Understanding the function of Fyn during tumourigenesis and development and in resistance to anticancer therapeutic agents can aid in the development and application of innovative medicines that specifically target this kinase, thus improving the management of cancers.